(untitled) (Revista Contexto & Saúde, 2026)
The objective of the study was to analyze the incidence and factors associated with victims of cardiopulmonary arrest. This is an exploratory, descriptive, longitudinal, retrospective, and quantitative study conducted by analyzing medical records and notification forms of patients admitted to the Adult Emergency Room of a public hospital in the interior of Minas Gerais, between January 2018 and December 2022, who presented with cardiopulmonary arrest. A data collection instrument was used that was designed and validated for content. Descriptive statistics, bivariate analysis, and the Logistic Regression Model were adopted for data analysis. Of the 224 patients, the majority were women (52.2%), elderly (71.6%), and married (44.6%). They had comorbidities (87.5%), especially systemic arterial hypertension and diabetes mellitus. Regarding the outcome, there is a prevalence of 85.3% of cases for deaths in less than 24 hours. It was found that asystole is a factor that predisposes to death, increasing the chance of this outcome by 5.13 times, as well as pulseless electrical activity and ventricular tachycardia to a lesser extent. Another important variable is a 0.35 increase in deaths among patients with respiratory diseases. It was concluded that the majority (85.3%) of victims of cardiopulmonary arrest die within the first 24 hours, and this outcome is associated with arrest rhythms characterized by asystole and ventricular fibrillation, as well as respiratory diseases.